(untitled) (International Journal of Environmental Sciences, 2025)
In today’s modern era,everyone wants to be super-fast with all the abilities to do the work accurate and well in time. Artificial Intelligence has a great impact in all the spheres of the economy. The financial advisory industry has been influenced by advances in technology, particularly the integration of Artificial Intelligence (AI). The main purpose of this study is to analyze the impact of AI-driven financial advisory services on investment decision-making.Furthermore, this study offers insights into the potential benefits and limitations of AI-based advisory services, helping investors, financial advisors, and technology developers make informed decisions about the future of AI.To achieve the objective of the study hypothetical data was formulated, a descriptive and exploratory research design and the review of related literature was made. The findings highlight the dual nature of AI’s influence—while it significantly improves investment decision-making efficiency, it does not entirely replace the human element in financial advisory services.This study begs for the more qualitative research to capture more new trends about the AI impact on investment decisions making as the AI is a dynamic concept in the environment of the investment.